The Application of Hand Massage in Reducing Pain Intensity in Patients After Laparatomy Surgery in Flamboyan 5 Ward, Dr. Moewardi Regional General Hospital of Surakarta - Sintya Diah Putri Astuti; Ika Silvitasari; Isti Wulandari (Al-Hijrah Indonesia, 2026)
Background: Laparotomy is a major surgical procedure associated with significant postoperative pain. While pharmacological management remains standard, non-pharmacological therapies such as hand massage offer complementary benefits for pain reduction. Objective: This study aimed to evaluate the effectiveness of hand massage in reducing pain intensity among post-laparotomy patients. Methods: A descriptive case study design was employed involving two patients recovering from laparotomy at Flamboyan 5 Ward, Dr. Moewardi Regional General Hospital, Surakarta. The intervention consisted of a 10-minute hand massage session conducted daily for three consecutive days. Pain intensity was measured using the Numerical Rating Scale (NRS) before and after each intervention. Results: Both participants demonstrated a reduction in pain scores following the intervention. Patient A's pain level decreased from 6 (moderate) to 1 (mild), while Patient W's decreased from 6 (moderate) to 2 (mild). The average reduction in pain scale was 4.5 points. Conclusion: Hand massage is effective in reducing pain intensity in post-laparotomy patients. It represents a safe, simple, and non-invasive option for non-pharmacological pain management in nursing care.